Baumgarten the Beautician. The Origins of Cosmetics as an Aesthetic Discourse - Nannini, Alessandro (Aesthetica Preprint, 2023)
In this essay, I intend to reconstruct the first encounter between the cosmetic discourse and the newly born aesthetic discipline in the German mid-eighteenth century. Examining the new aesthetic conceptualization of cosmetics, I aim to investigate both its significance within the cosmetic tradition and its implications for the rise of philosophical aesthetics with regard to the relationship with corporeal beauty.